PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNINGTIPECOURSE REVIEW HORAY BERBANTU MEDIA VIDEOPEMBELAJARAN TERHADAP HASIL BELAJAREKONOMI SISWA KELAS XI - Muhammad Rifa’i; Ningrum Ningrum (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
Learning is a process of interaction of learners with educators and learning resources in a learning environment. To achieve the purpose of learning it is necessary election or use of learning models in accordance with the material that will be taught so that the expectations of the material delivered using the selected learning model can cause positive effects for learners. The purpose of this study is "To determine the effect of the use of model Cooperative Learning Type Course Horay Course assisted learning video media to the students' economic learning outcomes class XI even semester MAN 1 Metro academic year 2017/2018. This study looks at how the influence of the use of cooperative learning model type course review horay assisted media learning videos on the results of study Economics. In thisdesign there is an experimental class and a control class that researchers will see the difference in achievement between the two classes. The method used is the method of collecting data on learning outcomes after students were given treatment is a test method. This research is a Quasi Experimental Design by using Design type of Non-equivalent Control Group Design with population class XI MAN 1 Metro academic year 2017/2018, the sample which is taken is class XI IPS4 as experiment class and class XI IPS1 as control class. The results can be seen from t count> t table, at a significant level of 5% that is 4.99> 1.70 thus Ha is accepted, that there is influence the use of cooperative learning model type course review horay by using media video learning to economic learning outcomes Students Class XI Even Semester MAN 1 Metro academic year 2017/2018.